(untitled) (Educational Dimension, 2024)
This paper examines the use of e-simulators as an effective tool for developing study skills in young learners in primary school. The advantages of e-simulators are discussed, including providing variable and unique tasks, immediate assessment, adjustable difficulty, and elements of competition and gaming. The paper outlines fundamental principles for designing effective educational e-simulators, such as generating interest, providing visual appeal and positive emotional background, encouraging critical thinking, allowing learner control, utilising personal devices, providing assistance and verifying results. Examples of e-simulators created by teachers-in-training using standard software tools like Microsoft Office and specialised design environments are provided. The capabilities of well-designed e-simulators can help ensure successful knowledge and skill acquisition by primary school students. Teachers can use the design principles and tools discussed to create customised e-simulators tailored to the needs of their students and lessons.